I Don't Want To Be Small - Anderson, Laura Ellen (New York : Philomel Books, 2021)
A young boy is frustrated because he is smaller than all his friends, but eventually he realizes that size does not matter when it comes to friendship.
Ages 3-7.
Grades K-1.
Keywords: Size perception -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Friendship -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Size -- Fiction; Self-acceptance -- Fiction; Friendship -- Fiction; Stories in rhyme; Picture books